STRATEGIC MANAGEMENT OPTIMIZATION THROUGH IFE AND EFE SWOT ANALYSIS - Dewi, Mega Septiana; Nenden Quratul Aini (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study aims to optimize the implementation of strategic management at Madrasah Aliyah Negeri (MAN) 2 Pamekasan through SWOT analysis, enriched with the IFE (Internal Factors Evalaution ) and EFE (External Factors Evaluation) frameworks. Adopting a sequential exploratory mixed-methods approach, qualitative and quantitative data were collected from various key stakeholders to comprehensively identify strategic factors. The results of the internal analysis (IFE) indicate that the madrasah's main strengths lie in its Adiwiyata predicate and unique skills programs, although it faces weaknesses in student and staff learning interest and discipline. From the external side (EFE), the biggest opportunity is the madrasah's position as an Islamic institution with added skills, amidst the threats of intense competition and shifting societal preferences. A synthesis of these findings yields four strategic assumptions: SO (leveraging strengths for opportunities), WO (addressing weaknesses with opportunities), ST (using strengths to face threats), and WT (minimizing weaknesses and avoiding threats). This research concludes that the optimization of strategic management at MAN 2 Pamekasan requires the implementation of concrete actions that are synergistic between internal and external factors, which in turn will enhance the madrasah's competitive advantage and sustainability.